RELASI KUASA DAN GENDER DALAM KASUS PEMERKOSAAN OLEH PELAKU HERRY WIRAWAN (Jurnal Nawala Politika, 2023)
Gender differences often provoke conflict which shows that the gender of women and men has different influence. Indonesia as an eastern cultured country is closely related to the assumption that it is bound by patriarchy through men with power and women under them. Feminism has become a political movement so that the genders of women and men have legal, social and cultural equality. Gender inequality can be seen from the fact that women are not a gender with a percentage that represents most of the decisions in the world. Power relations become one of the problematic backgrounds while talking about how different gender give different influence and opportunities in social life. The case by the perpetrator Herry Wirawan was in the spotlight in Indonesia which is closely related to culture and religion where the perpetrator was a teacher at the Islamic Boarding School who raped thirteen female studentscausing eight pregnancy while having nine babies in result.The perpetrator uses the power he has to influence other individuals making the rape case occurs. This case ended with a life imprisonment sentence given to the perpetrator, but this should be a highlight regarding how the court handled rape cases which had lasting effects from woman emotional state to the birth of babies from rape cases. Keywords: Power relations, gender inequality, discourse